Designing and Reporting Survival Analyses in Nursing Research: A Consensus Guideline and Checklist (STaRN-Survival) Covering Time-Dependent Covariates, Competing Risks, RMST, and Multistate Models - Villanueva, Maria Laisa D.; Reyes-Santiago, Fatima; Ploysong, Natcha; Kittipanya, Siriporn (Java Nursing Journal, 2026)
Background: Nursing time-to-event outcomes drive bedside and managerial decisions, yet many reports ignore time-varying exposures and competing risks, obscuring absolute benefits and harms. Robust estimands (cumulative incidence, RMST) and appropriate models are needed to quantify “how much,” “by when,” and “through which pathway” change occurs in routine care. Purpose: This study aimed to test the association of infection status, device exposure, and an early nurse-led care bundle with recovery and adverse events among inpatients. Methods: Prospective Philippine cohort (Feb–Mar 2025) enrolled 116 adults after exclusions. Baseline infection/comorbidity recorded; device exposure time-varying; early bundle ≤24h. Outcome: recovery with death/discharge competing. Used Aalen–Johansen, Cox, or Fine–Gray, RMST, sensitivity analyses. Results: Among 116 participants (49.1% female; comorbidity ≥ 3: 32.8%), recovery by 60 days was 67.2% overall, lower with baseline infection (54.3%) than without (74.5%); adverse-event risk was 18.1% overall and higher with infection (28.4% vs 12.8%). Infection was associated with slower recovery (cause-specific HR 0.68, 95% CI 0.52–0.89) and higher adverse events (sHR 1.71, 1.18–2.48). Time-dependent device exposure was unfavorable (HR 0.74, 0.56–0.97; sHR 1.52, 1.04–2.23). Early bundles improved recovery (HR 1.36, 1.08–1.72) and yielded ~+2.1 event-free days by day 50–55; findings were robust in sensitivity analyses. Conclusion: Infection control, device stewardship, and early standardized nursing bundles are timely, modifiable levers that accelerate recovery and reduce harms. Reporting absolute risks and RMST alongside hazards supports actionable, equitable improvement in inpatient nursing care. Relevance to clinical practice: These findings support prioritizing early nurse-led bundles, strict infection control, and device stewardship to shorten recovery time, reduce adverse events, and guide bedside and managerial decisions using absolute risks and RMST.